2019
DOI: 10.21769/bioprotoc.3128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mitochondrial Membrane Potential Using the Cationic JC-1 Dye as a Sensitive Fluorescent Probe

Abstract: In recent years, fluorescent dyes have been frequently used for monitoring mitochondrial membrane potential to evaluate mitochondrial viability and function. However, the reproducibility of the results across laboratories strongly depends upon following well validated and reliable protocols along with the appropriate controls. Herein, we provide a practical user guide for monitoring mitochondrial membrane potential in whole cells using a fluorescent cationic probe. The data analysis of mitochondrial membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
423
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(441 citation statements)
references
References 9 publications
14
423
0
4
Order By: Relevance
“…The JC-1 staining results obtained in our study also showed that THSG might have the ability to stabilize the mitochondrial membrane potential under conditions of H 2 O 2 -induced free radical damage in UB/OC-2 cells (Figure 5e). JC-1 is a cationic dye that enters and accumulates in negatively charged mitochondria and forms a red fluorescent JC-1 dimer that aggregates in healthy cells with a normal membrane potential [33]. Conversely, because an increased mitochondrial membrane permeability results in less negative mitochondria in unhealthy or apoptotic cells, the JC-1 dye does not accumulate to sufficiently high levels to reach the high concentration required for the formation of JC-1 monomer aggregates and continues to exhibit a green fluorescence [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JC-1 staining results obtained in our study also showed that THSG might have the ability to stabilize the mitochondrial membrane potential under conditions of H 2 O 2 -induced free radical damage in UB/OC-2 cells (Figure 5e). JC-1 is a cationic dye that enters and accumulates in negatively charged mitochondria and forms a red fluorescent JC-1 dimer that aggregates in healthy cells with a normal membrane potential [33]. Conversely, because an increased mitochondrial membrane permeability results in less negative mitochondria in unhealthy or apoptotic cells, the JC-1 dye does not accumulate to sufficiently high levels to reach the high concentration required for the formation of JC-1 monomer aggregates and continues to exhibit a green fluorescence [33].…”
Section: Discussionmentioning
confidence: 99%
“…JC-1 is a cationic dye that enters and accumulates in negatively charged mitochondria and forms a red fluorescent JC-1 dimer that aggregates in healthy cells with a normal membrane potential [33]. Conversely, because an increased mitochondrial membrane permeability results in less negative mitochondria in unhealthy or apoptotic cells, the JC-1 dye does not accumulate to sufficiently high levels to reach the high concentration required for the formation of JC-1 monomer aggregates and continues to exhibit a green fluorescence [33]. H 2 O 2 rapidly depolarized the mitochondrial membrane potential, which indicated mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours later, the JC-1 assay was conducted, followed by flow cytometry. The details were described previously (6). JC-1 dye obtained from Thermo Fisher Scientific (Waltham, MA, USA).…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…To further evidence ER stress-induced mitochondrial dysfunction and investigate the impact of EUK-134, normalised respiratory flux control ratios were determined using the six parameters of mitochondrial function [21]. A significant decline was found in respiratory control ratio (RCR), phosphorylating respiration, and coupling efficiency under ER stress, which were inhibited by antioxidant treatment (Figure 2H).…”
Section: Mitochondrial Oxygen Consumption and Mitochondrial Unfoldedmentioning
confidence: 99%